THEORETICAL FRAMEWORK FOR NATIONAL PENSION SYSTEMS FORMATION AND DEVELOPMENT - Martynenko N.V. (Pressing Problems of Public Administration, 2018)
A theoretical analysis of models is conducted, based on which a classification of pension systems is created; a review of theoretical approaches to their research is made, providing certain reference points for elaboration of the main lines of development of a pension system for a modern state.